Sisterhood Against Patriarchy in Moxie (2021) - Kusumaningtyas, Dela Wahyu (Journal of Indonesian Literacy and Indigenous Culture, 2025)
Sisterhood, in the context of feminist theory, refers to the deep bond and solidarity among women that empowers them to support one another and collectively resist systems of oppression. This study examines the portrayal of sisterhood as a form of collective resistance against patriarchy in Moxie (2021). Using bell hooks’ feminist theory of sisterhood as the primary analytical framework, the research explores how solidarity among female characters functions as an emotional support system and a trigger for collective action. The objectives of the study are to analyze how sisterhood is depicted throughout the movie and to investigate how it leads to collective action to challenge entrenched patriarchal norms within the high school setting. Employing qualitative descriptive methods, including close reading and in-depth analysis of dialogues, scenes, and character interactions, the study finds that sisterhood in Moxie (2021) is expressed through mutual support, compassion, sharing resources and strengths, unity, and collaboration. Additionally, the findings demonstrate that sisterhood inspires collective action by fostering innovation, motivation, shared experiences, and empowerment through solidarity. This research contributes to feminist literary and criticism by highlighting the role of female solidarity as an effective strategy for resisting systemic gender oppression and promoting social change.